ANALISIS NUMERIK DAMPAK BRACKET PADA STRUKTUR TROLI MESIN TEMPEL MENGGUNAKAN METODE ELEMEN HINGGA - Anggra Fiveriati; Eli Novitasari; IGNB Catrawedarma; Achdri Fauzi; Jangka Rulianto; Tomy Jepisa (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
This study evaluates the structural enhancement of an outboard engine trolley through topology optimization of a reinforcement bracket using the finite element method (FEM). The trolley, made of 6061-T6 aluminum, was subjected to a vertical load of 75 kg (735.5 N). The topology optimization was formulated with the objective of minimizing structural compliance (maximizing stiffness) subject to a 60% volume fraction constraint and maintaining a safety factor above the allowable limit of 1.25. Three configurations were analyzed: without bracket, with a conventional bracket, and with a topology-optimized bracket. The structural responses were evaluated in terms of total deformation, Von Mises stress, and safety factor. The optimized bracket reduced maximum deformation from 1.017 mm to 0.557 mm and decreased maximum stress from 87.214 MPa to 72.062 MPa. The safety factor increased from 3.153 to 3.816, indicating improved structural reliability. The results demonstrate that topology optimization effectively enhances stiffness and strength while enabling efficient material utilization under vertical loading conditions.